Protein–polysaccharides of Trametes versicolor: production - Arteiro, J M (2012)
Abstract Extracellular- (E-PPS) and intracellular-protein– polysaccharides (I-PPS) complexes were produced by Trametes versicolor in submerged cultures with different carbon sources. The highest extracellular-(EPS) and intracellular- polysaccharide (IPS) concentration in the complexes was obtained with tomato pomace culture. DPPH radical scavenging for E-PPS and I-PPS produced by liter of culture was equivallent to 2.115 ± 0.227 and 1.374 ± 0.364 g of ascorbic acid, respectively. These complexes showed a protector effect in the oxidation of erythrocyte membranes and had ability to inhibit the hemolysis and methemoglobin synthesis in stressed erythrocytes. These results suggest that extracellular- and intracellular- polysaccharides produced are important bioactive compounds with medicinal potential.